Pengaruh Terapi Alquran Terhadap Penurunan Tingkat Stres Mahasiswa Keperawatan di PSIK UMI Makassar - Munir, Nur Wahyuni; Najihah, Najihah; Lutia, Trisulawati (Poltekkes Kemenkes Kendari, 2021)
Stress is the body's reaction to the environment that is considered dangerous. Metabolism and blood circulation become disturbed if the psychiatric feel depressed which can cause illness. This study aims to determine the effect of therapy of the Qur'anic verses on reducing stress levels in nursing students in completing their thesis at the Muslim University of Indonesia. This type of research uses a quasi-experimental with one group pre-post design on 18 respondents using purposive sampling technique. The research instrument used a questionnaire. The statistical test of the paired sample test shows the value of p = 0.042 with ? = 0.05. The results showed that the stress level of students compiling their thesis at the Muslim University of Indonesia decreased from 88.9% to 66.7% after being given therapy for the Qur'anic verses. The conclusion of this study is that there is an effect of the therapy of Qur'anic verses on reducing stress levels in nursing students in completing theses at Muslim University of Indonesia and there are differences in student stress levels in preparing theses at Indonesian Muslim University before and after receiving verse therapy.